Fiestas Patrias 1990 - Parade, Fiesta, and Awards Luncheon - Castellano, Alcario:::creator::::::::::::
Video and transcripts of the Fiestas Patrias Parade and Fiesta, presented by the San Jose chapter of the American GI Forum. Featuring Little Joe Hernandez as the Grand Marshal. Also included is the Fiestas Patrias Parade Awards Luncheon held on September 22, 1990 at the Eastside Senior Center,